Book Review: J. Kurowicki, Estetyczność środowiska naturalnego/Ecoaesthetics of the Natural Environment - Papuziński, Andrzej (Problemy Ekorozwoju, 2011)
The reviewed book does not contain an attempt to develop an eco-aesthetics in accordance with the presented postulate, which is understandable in the light of the aesthetics inscribed in its concept: as an obligation of epistemology not to provide tools. On the other hand, it is eloquently aged, which eco-aesthetics should not be. In this respect, the full Socratic values ​​of philosophy as enlightenment are obtained, which cure people from naivety.